Perfis de adaptação psicológica na criança com asma - Lima, Lígia (2010)
This study aims at the characterization of children with asthma and the identification of patterns of psychological adjustment. The sample consisted of 89 children, from both sexes and aged between 8 and 12 years old with physician’s diagnosed asthma. Measures of temperament, intelligence, self-esteem, frequency and efficacy of coping strategies, symptoms of anxiety/depression, social abilities and generic quality of life were used and cluster analysis were conducted. The results found suggest that children with asthma, as a group, have characteristics that imply greater difficulties in terms of psychological adaptation. Nevertheless cluster analysis revealed the existence of two distinct profiles in terms of adjustment and showed that although asthma represents a risk of psychological desaptation it is possible to cope positively wth the disease.